The adjunct role of pharmacotherapy in multimodal treatment of paediatric functional neurological disorder - Rynagh Cummins; Clare Hawkes; Clare Hawkes; Clare Hawkes; Judy Longworth; Stephen Scher; Stephen Scher; Kasia Kozlowska; Kasia Kozlowska; Kasia Kozlowska (Frontiers in Psychiatry)
BackgroundRehabilitation for children with functional neurological disorder (FND) requires a biopsychosocial intervention: physiotherapy, psychotherapy, pharmacotherapy, school attendance, and family work. This study documents the pharmacotherapeutic element and its rationale.MethodsMedication use was documented in 158 children with FND (41 boys, 117 girls, aged 8.50–17.58; mean 13.78) admitted into the Mind-Body Program.ResultsOn presentation, children with FND had high levels of functional impairment, school loss, and comorbid psychiatric, functional, and medical disorders. On admission, 63% (n=95) were on medications. During admission, 130 (82.3%) children had pharmacotherapy interventions: dose adjustment, initiation, or discontinuation. 88.6% (n=140) were discharged on medications. Pharmacotherapy targets included: antidepressants for anxiety/depression (n=111; 70.3%); antipsychotics for extreme anxiety/arousal (n=73; 46.2%); melatonin for sleep (n=64; 40.5%); α agonists and β blockers, for arousal, sleep initiation, and trauma-related nightmares (n=58; 36.7%); iron/vitamin supplementation (n=30; 19.0%); and medications for functional gut symptoms (n=28; 17.7%) and comorbid pain (n=20; 12.7%).ConclusionsPharmacotherapy is used as an adjunct in paediatric FND to down-regulate the stress system, reset the circadian clock, manage pain, and treat comorbid disorders. Pharmacotherapy and its concomitant placebo effects scaffold the child to enable engagement in all components of the therapeutic process and return to healthy function.